Molecular Link between Circadian Rhythmicity and Mood Disorders - Faltraco, Frank; Palm, Denise; Coogan, Andrew; Simon, Frederick; Tucha, Oliver; Thome, Johannes (Current Medicinal Chemistry, 2022)
Background: The internal clock is driven by circadian genes [e.g., Clock, Bmal1, Per1-3, Cry1-2], hormones [e.g., melatonin, cortisol], as well as zeitgeber [‘synchronisers’]. Chronic disturbances in the circadian rhythm in Objectives: The aim of this review is to summarise the current knowledge and literature regarding circadian rhythms in the context of mood disorders, focussing on the role of circadian genes, hormones, and neurotransmitters. Methods: The review presents the current knowledge and literature regarding circadian rhythms in mood disorders using the Pubmed database. Articles with a focus on circadian rhythms and mood disorders [n=123], particularly from 1973 to 2020, were included. Results: The article suggests a molecular link between disruptions in the circadian rhythm and mood disorders. Circadian disturbances, caused by the dysregulation of circadian genes, hormones, and neurotransmitters, often result in a clinical picture resembling depression. Conclusion: The article suggests a molecular link between disruptions in the circadian rhythm and mood disorders. Circadian disturbances, caused by the dysregulation of circadian genes, hormones, and neurotransmitters, often result in a clinical picture resembling depression.
Keywords: mania